Estimación de las pérdidas mediante la protección de frutos de Guanábana contra el ataque del perforador de semilla (Bephratelloides maculicollis) Hymenoptera eurytomidae - Arévalo Reátegui, Jorge Oswaldo (2012)
This project was conducted in order to find methods of control against seed borer attack (Bephratelloides maculicollis), developed between february and december 2011, at the Experimental Station "Juan Bernito" Tropical Crop Institute located in the districted of Banda Shilcayo, province and department of San Martin, which had as main objective to protect the fruits of "soursop" (Annona muricata L) from attack seed borer, a major pest of this crop. Insect pests of "soursop" affect virtually all plant structures, which generally are more abundant and complex in its handling. The attack of this pest can cause up to 70% reduction in production, coming to be several holes in the fruit. One of these control techniques was bagging or exclusion of fruits (T1 - perforated plastic bags), bags used were 305 mm x 505 mm, perforated and transparent. They protect all the fruits of the 12 plants evaluated of that treatment, fruit of 7 cm, large enough for the bagging of fruit, heart-shaped sea urchins for evaluation of length, width, weight and percentage of incidence of the pest and / or examine the presence of disease. Another technique used was the application of insecticide (T2 - cypermethrin) this was done every 30 days for the duration of the project and (T3 - azadirachtin) and plant extract, it was the respective grinding Neem with water, the application of this extract was performed every 20 days. For these treatments was weekly assessment is scored each fruit that showed the heart shaped sea urchins, the time of harvesting was carried to the laboratory for their respective measurements and observations. These treatments were performed in order to reduce costs and negative environmental impact generated by the chemical control. Within the infested fruit was observed, the insect collecting and photographing male and female, causing the holes that weaken the quality of the fruit.